Intestinal Obstruction due to Bezoar in Elderly Patients: Risk Factors and Treatment Results - Fatih Altintoprak; Eyup Gemici; Yasin Alper Yildiz; Mustafa Yener Uzunoglu; Taner Kivilcim (Emergency Medicine International)
Purpose. Bezoars are foreign particles from the accumulation of indigestible materials in the gastrointestinal system and a rare cause of mechanical intestinal obstruction. We aimed at investigating differences in risk factors for the development of intestinal obstruction associated with bezoar in elderly patients. Methods. Hospital records of patients who underwent surgery associated with phytobezoar between January 2004 and May 2016 were retrospectively evaluated. Patients were divided into two groups [<65 years (Group 1) and ≥65 years (Group 2)]. Data were examined regarding presence of comorbidity, history of abdominal surgery, operation time, bezoar site, surgical technique, length of hospitalization, morbidity, and mortality. Results. Of 121 patients enrolled, 48 (39.7%) were male and 73 (60.3%) were female (range: 24-86 years). Group 1 consisted of 69 patients aged < 65, while Group 2 consisted of 52 patients aged ≥ 65. Comorbidity was reported in 52 (42.9%) patients (mostly diabetes mellitus, 20.7%), while 60 patients (49.6%) had history of abdominal surgery (mostly peptic ulcer, 27.3%). No statistical differences were found between the two groups in terms of sex, bezoar site, surgical technique preferred, history of abdominal surgical intervention, pre- and postoperative CT examination, morbidity rates, and length of hospitalization. But, ratio of peptic ulcer operations history, presence of total comorbidity, and time of surgery decision was higher in Group 2 patients. Conclusion. In bezoar-related intestinal obstruction, duration and outcome of treatment are not affected by age distribution. Possibility of bezoar should primarily be considered in elderly patients with history of peptic ulcer operation.